Tea Plantations and Socio-Cultural Transformation: The Case of Assam (India) - Chandra Kala Magar; Bimal Kumar Kar (Space and Culture, India, 2016)
The tea plantations of Assam, which constitute the country’s 53.97 per cent tea area, 49 per cent tea worker population, and 52.04 per cent tea production, occupy an important place in the economy, culture and polity of the state. The onset of tea plantations during British colonial rule has not only changed the landscape of the upper Brahmaputra valley through green tea bushes being nourished by tea tribes from east-central India, but also evolved a distinct tea culture. Although formation of small tea growers has added a new dimension to the growth of tea industry of Assam in recent times, the culture that emerged due to the long continued interaction of British planters, tea worker tribes and indigenous Assamese is well reflected in the language, way of life, work culture, food habits and many other socio-cultural practices in most of the large tea estates in the state. In fact, the impact of tea culture is so penetrative that it has been able to bring about development in the form of tea festival, tea tourism, tea folk songs and dances, etc. in the state. An attempt is made in this paper to explore the role of tea plantation and the people associated with it to the socio-cultural transformation of Assam based on both secondary data and primary data through field study. The primary data have been collected from selected tea estates, tea garden worker colonies, tea-tribe villages and urban dwellers.